Analisis Hukum Positif Pengupahan Berdasarkan Peraturan Pemerintah Nomor 36 Tahun 2021 Tentang Pengupahan - Ridho Alvian (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
The key to the progress of a country is to see the economic growth in that country. In advancing and growing the country's economic activities, of course, workers or laborers and employers play an active role in advancing the economy of a country, the most important aspect in the world of economics involving these two parties is of course about wages, this is the minimum wage that must be received by workers and provided by employers. In the wage paradigm, of course, there are regulations that have been formed to determine the systematics and methods of calculating wages, this is stated in Government Regulation concerning Wages. In completing the research, researchers used a qualitative method of literature. This research discusses three main problems, namely the rights received by workers, how the minimum wage is calculated, and the implementation of the minimum wage for UMP and UMKM..